Analyzing The Implementation of Neuro Linguistic Programming on Islamic Religious Education: A Philosophical Perspective - Ahsin, Nurul; Thoriquttyas, Titis (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Abstract This research aims to analyze the implementation of the Neuro Linguistic Program (NLP) in Islamic Religious Education (IRE) learning through two educational philosophy perspectives, namely Islamic Educational Philosophy (IEP) and Educational Philosophy (EP). This research focuses on the description and elaboration of the philosophical schools contained in the implementation of NLP to IRE. The formulation of the problem proposed in this study is how to analyze the implementation of NLP in IRE learning from the perspective of educational philosophy and Islamic education philosophy? This study uses a qualitative method, where researchers optimize the literature review approach. Researchers collected articles and research results with the keywords,